MUSIK DAN PUISI SEBAGAI MEDIA AKULTURASI BUDAYA TIONGHOA DAN SUNDA DI KOTA BANDUNG - Santi Susanti; Kismiyati Elkarimah (Jurnal Akrab Juara, 2019)
He also chose poetry and music as a way to show his love for Sundanese. This paper aims to express the meaning of kasundaan for Soeria Disastra, how is this meaning manifested in everyday behavior? And what motives behind Soeriadisastra love Sundanese. Using qualitative phenomenological methods, research data was obtained through interviews and documentation studies related to the theme. The results showed that the family environment and social environment had an influence on the growth of love for Sundanese culture. The taste was mediated through poetry and music by establishing the Kota Kembang Choir, which performed Sundanese songs. Soeria, interpreted kasundaan as Sundanese characteristics, in language, culture and society. Culturally, Soeria defines kasundaan as a culture that has a unique and dynamic beauty. This uniqueness brings pride to Soeria because she can enjoy it. Born and raised in different environments, namely the Chinese family environment and the Sundanese society, making the soul of Soeria rich, which is a combination of Chinese from the physical and Sundanese culture of the values ​​learned. He also felt that he had fused with Sundanese culture.